Analisis Fitur Swap Free pada Platform Trading Forex dalam Perspektif Majelis Ulama Indonesia (MUI) - Noviasih, Ajeng; Hadiati, Teti (el hisbah Journal of Islamic Economic Law, 2025)
Forex trading is a form of trading one currency for another that is done by utilizing fluctuations in currency exchange rates at certain times. However, there are concerns about its compatibility with sharia law. PT Finex Bisnis Solusi Futures presents an Islamic Account to avoid overnight fees (interest) or Swap free. The word “Islamic” claims this feature is sharia compliant, although the transaction mechanism is allegedly the same as forex trading without Swap free, which is still under debate. Forex trading is in accordance with the pillars of Al-Sharf, but spot or cash payments are still not fulfilled. This research aims to explain the mechanism of forex transactions with the swap free feature at Finex and analyze its suitability with the DSN MUI Fatwa No. 28/DSN-MUI/III/2002 concerning buying and selling currencies (Al-Sharf).This research is included in the category of empirical legal research using a qualitative approach. Data sources in the form of primary data obtained by observation techniques carried out on the forex trading platform owned by PT Finex Solusi Bisnis Futures and the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) Fatwa No. 28/DSN-MUI/III/2002 concerning currency trading transactions (Al-Sharf), and secondary data containing primary legal materials, secondary legal materials, and tertiary legal materials obtained by documentation techniques consisting of material or data related to forex trading, books, journals, research documentation, and other sources. This research uses a qualitative descriptive data analysis method.The results of this study conclude that the mechanism of forex trading transactions using the swap free feature or Islamic Account begins with registering an account on the Finex platform, conducting market analysis, determining transaction positions, and making transactions. The Swap free feature (Islamic Account) is not yet in accordance with the. provisions of DSN-MUI No.28/DSN-MUI/III/2002 concerning the sale and purchase of currencies (Al-Ṣharf) because it still utilizes currency exchange rate fluctuations, is not done in cash, uses a leverage system and performs short selling strategies aimed at profit.